Hypoxia inducible factor-1-dependent up-regulation of BMP4 mediates hypoxia-induced increase of TRPC expression in PASMCs - Wang, Jian (Cardiovasc Res, 2015)
AIMS: Previously we demonstrated that both hypoxia inducible factor-1 (HIF-1) and bone morphogenetic protein-4 (BMP4) up-regulate transient receptor potential canonical (TRPC) 1 and TRPC6, resulting in increased basal intracellular Ca(2+) concentration ([Ca(2+)](i)) in pulmonary arterial smooth muscle cells (PASMCs), driving development of chronic hypoxia (CH)-induced pulmonary hypertension (CHPH). This study aims to determine whether HIF-1 regulates BMP4, and whether BMP4 mediates TRPC and basal [Ca(2+)](i) increases in hypoxic PASMCs. METHODS AND RESULTS: The level of BMP4 mature protein was increased for ∼183% in distal pulmonary arterial smooth muscle (PA) from CH (10% O(2) for 21 days; CH) exposed rats, and 143% in PASMCs cultured under prolonged hypoxia (4% O(2) for 60 h). In rat PASMCs, HIF-1α overexpression up-regulated, whereas HIF-1α knockdown under hypoxia decreased BMP4 expression; site-mutation identified two functional HIF-1-binding sites in Bmp4 gene promoter; noggin or BMP4 siRNA treatment blocked hypoxia-induced increases of TRPC1 and TRPC6 expression and basal [Ca(2+)](i). Likewise, in mice, exposure to CH increased BMP4 expression in distal PA for ∼80%, which was absent in HIF-1α heterozygous mutant mice. Comparing with wild-type littermates, BMP4 heterozygous mutant mice exposed to CH displayed lower BMP4 and TRPC levels in PA, decreased basal [Ca(2+)](i) in PASMCs, and attenuated CHPH. In human PASMCs, HIF-1α knockdown attenuated hypoxia-induced BMP4 expression and knockdown of either HIF-1α or BMP4 abolished hypoxia-induced TRPC expression and basal [Ca(2+)](i). CONCLUSIONS: BMP4 acts downstream of HIF-1 and mediates hypoxia-induced up-regulation of TRPC, leading to increased basal [Ca(2+)](i) in PASMCs, promoting CHPH pathogenesis.